2017
DOI: 10.2217/epi-2017-0039
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Dna Methylation Drives Human Embryonic Stem Cell Erythropoiesis by Remodeling Gene Expression Dynamics

Abstract: Aim:To investigate the role of DNA methylation during erythrocyte production by human embryonic stem cells (hESCs). Methods: We employed an erythroid differentiation model from hESCs, and then tracked the genome-wide DNA methylation maps and gene expression patterns through an Infinium HumanMethylation450K BeadChip and an Ilumina Human HT-12 v4 Expression Beadchip, respectively. Results: A negative correlation between DNA methylation and gene expression was substantially enriched during the later differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…We found that approximately 69% of DMCs associated with CpG islands were located in promoter regions (Table 2). Liu et al (Liu et al, 2017) reported that the proportions of hypermethylated CpG sites located in CpG islands, CpG shores and other locations were 25.49∼34.23%, 21.57∼40.75%, and 25.02∼52.94%, respectively, during different stages of human embryonic stem cells. Genes that contained differentially methylated regions (DMRs) in their first intron were more than the genes that contained DMRs in their promoter and their first exon (Anastasiadi et al, 2018), which are the same trend as this study (Supplementary File S1).…”
Section: Discussionmentioning
confidence: 99%
“…We found that approximately 69% of DMCs associated with CpG islands were located in promoter regions (Table 2). Liu et al (Liu et al, 2017) reported that the proportions of hypermethylated CpG sites located in CpG islands, CpG shores and other locations were 25.49∼34.23%, 21.57∼40.75%, and 25.02∼52.94%, respectively, during different stages of human embryonic stem cells. Genes that contained differentially methylated regions (DMRs) in their first intron were more than the genes that contained DMRs in their promoter and their first exon (Anastasiadi et al, 2018), which are the same trend as this study (Supplementary File S1).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an association between IL6/JAK/STAT DNA altered methylation and depression has been recently described (Ryan et al., 2017). JAK and STAT gene hypomethylation might also exert influences on erythroid lineage choice by specifically upregulating erythropoiesis transcription factors (Liu et al., 2017). In B cells activating pathway, the lysine-specific histone methyltransferase KMT2D affected H3K4 methylation and expression of a specific set of JAK-STAT genes (Figure 2B; Ortega-Molina et al., 2015).…”
Section: Epigenetic Control Of Il-6/jak/stat Pathwaymentioning
confidence: 99%
“…Previous studies have demonstrated that abnormal DNA methylation led to gastric carcinogenesis by either hyper-methylating several tumor-suppressive miRNAs [ 3 5 ] or hypo-methylating onco-miR [ 6 ]. In addition, DNA methylation also regulated the erythropoiesis of embryonic stem cell [ 7 ], the pathogenesis of idiopathic pulmonary fibrosis [ 8 ], the neurodevelopment of the human hippocampus [ 9 ], and other processes. In addition to regulating disease pathogenesis, DNA methylation also performs long-term regulatory activities.…”
Section: Introductionmentioning
confidence: 99%